Social control in the municipal planning of education in Brazil - Souza, Donaldo Bello de; Alcântara, Alzira Batalha (Education Policy Analysis Archives, 2017)
Throughout the process of redemocratization of Brazil (1980s), social control was synonymous with civil control by the State, aimed at the construction new social projects from an emancipatory, democratic and participative perspective. Starting in the 1990s, the concept became depoliticized from a conservatory and neoliberal perspective, creating channels of instrumental and centralized participation, bureaucratization, and segmentation. This article deals with the problems concerning social control in the scope of the municipal planning of education, focusing on the Monitoring and Social Control Council (MSCC) and the Municipal Education Council (MEC). the study considered 20 (95%) of 21 Municipal Plans of Education (MPEs) of the Metropolitan Region of Rio de Janeiro (MRRJ), aligned with the new National Plan of Education (NPE) to the decennial 2014-2024, and analyzed the role attributed to these collegiate bodies in the sphere of localized social control of education. It is concluded that the MPEs reflect the statements of the NPE regarding social control and the correlated bodies (MSCC and MEC), but in a fragmented and sparse way, due to the relatively small the systematic incorporation of these actions and of the Councils roles in the decisions. It is also possible to affirm that these results express a continuation of a prescriptive failure that has lasted since the previous decennial planning (2001-2011), since these plans did not attribute a highlighted place to the Councils, thus weakening the systematic social control of education at the municipal, intermunicipal, and metropolitan planning levels.